Mengembangkan Kreativitas Anak Melalui Media Benang Warna pada Anak Usia Dini - Devi Sinta Sagala; Humaidah Br Hasibuan (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Creativity is the ability in a person to form and provide novelty in the form of ways, ideas and ideas that can benefit the person himself and the surrounding environment. Independent nature, skills and also the ability to solve problems are emphasized in children's creativity. The formulation of the research problem this time is "How to develop children's creativity by using a color image creation using colored thread by children aged 5-6 years at RA Muslimat Al-washliyah Simangalam, South Kualuh District, Labuhan Batu Regency, North Sumatra?”, The purpose of this research is to develop children's creativity through a color game using thread media at the age of 5-6 years at RA Muslimat Al-ashliyah Simangalam, South Kualuh District, Labuhan Batu Regency, North Sumatra. This study uses descriptive qualitative research in which the research subjects are teachers and also students in class B. The data collection tools that the authors use in this study are observation, interviews and documentation. Based on the results of the analysis and discussion that the researchers did for one month at RA Muslimat Al-washliyah Simangalam, South Kualuh District, Labuhan Batu Regency, North Sumatra in developing the creativity of students through color games that are mediated with colored threads when carrying out learning activities and playing with threads in activities carried out to develop creativity in children. at the end of the activity developing children's creativity using these threads is considered effective because there are more children who develop according to expectations than children who have not yet developed. Keywords: Early Childhood Education, Creativity